Removal of metallic foreign bodies embedded in soft tissues by stereotaxic approach - Ceylan, Mehmet Fethi (Afr Health Sci, 2014)
BACKGROUND: A trial fibrillation (AF) is the most common cardiac arrhythmia and increases the risk of stroke and death. Patients with hypertensive have an increased risk of developing atrial fibrillation. RDW (Red blood cell distribution width) levels are elevated in cardiovascular disorders including heart failure, stable coronary disease, acute coronary syndrome, slow coronary flow and stroke. OBJECTIVE: To investigate the relation between RDW and AF in patients with hypertensive METHOD: We retrospectively examined 126 consecutive hypertensive patients (63 hypertensive patients with AF and 63 hypertensive patients without AF matched with age and sex RESULTS: The mean age of the study population was 71,09± 8,50 (af group) and 70,97±8,24 (non-af group) years. RDW level was different among patients with atrial fibrillation and without atrial fibrillation.(15,13±1,58 and 14,05±1,15 p<001). Logistic regression analysis showed that RDW and left atrial dimension were only independently risk factory associated with atrial fibrillation. (Rdw odds ratio:1,846 CI; 1,221–2,793 p<0,05). Roc curve analyses were applied to determine the cut-off point. Cut-off point was at 14,195 and Sensitive, specificity was %71,4, %56 respectively. CONCLUSION: RDW levels were higher in hypertensive patients with atrial fibrillation. An increased RDW level in the patient with hypertension may alert physician on developing or presence of atrial fibrillation.